Mericarpmorphometry and morphology of five Ferula species from the Ulytau region, Central Kazakhstan - AIZAT SHARIP; SARDARBEK ABIYEV; GULNARA SITPAYEVA; KANAT KULYMBET; BEKTEMIR OSMONALI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sharip A, Abiyev S, Sitpayeva G, Kulymbet K, Osmonali B. 2026. Mericarpmorphometry and morphology of five Ferula species from the Ulytau region, Central Kazakhstan. Biodiversitas 27 (6): d270610. https://doi.org/10.13057/biodiv/d270610. This study presents a comparative morphological and morphometric analysis of mericarps from five Ferula species (Apiaceae) associated with the Ulytau region of Central Kazakhstan: Ferula karelinii, Ferula teterrima, Ferula varia, Ferula songarica, and Ferula ferulaeoides. A total of 150 mericarps (30 per species) were analyzed. Qualitative characters included mericarp size, color, shape, groove pattern, surface texture, and chalazal-end morphology, while quantitative parameters comprised mericarp mass and linear dimensions (length, width, diagonal length, apical width, and basal width). The results revealed clear interspecific differences in both qualitative and quantitative traits. The largest mericarps were recorded in F. karelinii, whereas the smallest were observed in F. ferulaeoides. Correlation analysis demonstrated strong positive relationships among linear mericarp parameters (r = 0.82–0.97), indicating a high degree of morphological integration. Regression analysis based on pooled data showed significant positive relationships between mericarp mass and dimensional traits (R² = 0.47-0.63; p<0.001). However, these relationships mainly reflected differences among species rather than consistent within-species allometric patterns. Species-specific analyses revealed considerable variation in mass–size relationships, including weak or negative correlations in some taxa. Although the relatively limited sample size and restricted geographic coverage require cautious interpretation, the results indicate that mericarp morphology and morphometry provide useful characters for comparative carpological studies of Ferula. Further research incorporating broader sampling, population-level analyses, and integrative taxonomic approaches is needed to evaluate the wider systematic significance of these traits.